REVITALISASI PEMBELAJARAN ILMU USHUL AL-FIQH DI PTAI - Andriyaldi, Andriyaldi (Alhurriyah, 2011)
As one important branch of Islamic science, the science of usul al-fiqh occupies a crucial position. In the real fact, itâ€™s maybe globally as a key science or the gate of the Islamic sciences. This view is not exaggerated, because the text of Islamâ€™s doctrine of understanding is largely determined by the discipline of usul al-fiqh. Therefore it is not surprising and very logicaly if the Islamic scholars earlier (â€˜ulama) they put the usul al-fiqh as the science of logic (mantiq) of all the teachings of Islam. More specifically, if the key philosophy of science is the science of Greek logic, especially logic Aristotele, then the system logic of the teachings of Islam itself is the science of usul al-fiqh. However, the question that arises is the lack of interest in usul al-fiqh. This analysis can be seen in some of the side as described in this paper and presented some offers solutions to usul al-fiqh revitalization back and beneficial in many areas of life such as political issues, economics, education, environment and others. This is the meaning of fiqh in the broadest sense and universal. So, itâ€™s look clearly related between â€œfiqhâ€ (islamic law) and usul al-fiqh of Islamic scholarly discourse.